2020
DOI: 10.1038/s41590-020-0783-5
|View full text |Cite
|
Sign up to set email alerts
|

Lung mesenchymal cells elicit lipid storage in neutrophils that fuel breast cancer lung metastasis

Abstract: Acquisition of a lipid-laden phenotype by immune cells has been defined in infectious diseases and atherosclerosis, but remains largely uncharacterized in cancer. Here, in breast cancer models we found that neutrophils are induced to accumulate neutral lipids upon interaction with resident mesenchymal cells (MCs) in the pre-metastatic lung. Lung MCs elicit this process through repressing the adipose triglyceride lipase (ATGL) activity in neutrophils in prostaglandin E2-dependent and -independent manners. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 51 publications
2
129
0
Order By: Relevance
“…PMN-MDSCs in the premetastatic niches may facilitate the escape of tumour cells by suppressing immune cells, inducing matrix remodelling and promoting angiogenesis 55 , which in turn facilitate the engraftment of tumour cells. Another mechanism of regulation of tumour metastasis was described in a recent study by Li et al 56 , who demonstrated, in a breast cancer model, that neutrophils accumulated neutral lipids via the repression of adipose triglyceride lipase activity. Neutrophil-specific deletion of adipose triglyceride lipase decreased metastasis in mice and lipid transfer from neutrophils to tumour cells was shown to facilitate metastasis 56 .…”
Section: Roles Of Mdscs In Cancermentioning
confidence: 90%
See 1 more Smart Citation
“…PMN-MDSCs in the premetastatic niches may facilitate the escape of tumour cells by suppressing immune cells, inducing matrix remodelling and promoting angiogenesis 55 , which in turn facilitate the engraftment of tumour cells. Another mechanism of regulation of tumour metastasis was described in a recent study by Li et al 56 , who demonstrated, in a breast cancer model, that neutrophils accumulated neutral lipids via the repression of adipose triglyceride lipase activity. Neutrophil-specific deletion of adipose triglyceride lipase decreased metastasis in mice and lipid transfer from neutrophils to tumour cells was shown to facilitate metastasis 56 .…”
Section: Roles Of Mdscs In Cancermentioning
confidence: 90%
“…Another mechanism of regulation of tumour metastasis was described in a recent study by Li et al 56 , who demonstrated, in a breast cancer model, that neutrophils accumulated neutral lipids via the repression of adipose triglyceride lipase activity. Neutrophil-specific deletion of adipose triglyceride lipase decreased metastasis in mice and lipid transfer from neutrophils to tumour cells was shown to facilitate metastasis 56 . The authors reported that these cells suppressed NK cells, suggesting that they may be PMN-MDSCs.…”
Section: Roles Of Mdscs In Cancermentioning
confidence: 90%
“…This work demonstrates that optical imaging of Bodipy FL c16 is important for lipid metabolism research. These studies are paramount to the successful translation of targeted metabolic therapies for TNBC and the plethora of other tumors that are dependent on fatty acids [ 57 , 63 , 82 ]. The drug screening protocol demonstrated here could also be applied to image the lung, liver, or brain through abdominal or cranial window chamber models, respectively [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug screening protocol demonstrated here could also be applied to image the lung, liver, or brain through abdominal or cranial window chamber models, respectively [ 83 , 84 ]. Tumors in each of these locations have reportedly shown a dysregulated lipid metabolism [ 82 , 85 , 86 ]. More invasive window chambers of non-superficial organs, such as liver or lung windows, would require terminal imaging sessions; therefore, only single time points could be captured without more advanced surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils also serve as an energy source to fuel metastatic tumor cells. In a breast cancer model, infiltrating neutrophils are induced to store lipids upon interaction with resident mesenchymal cells in the lung so that when disseminated tumor cells (DTCs) arrive, neutrophils transfer their stored lipids to DTCs for their survival and proliferation (Li et al, 2020).…”
Section: Secondary Organ Colonizationmentioning
confidence: 99%